The Association of Biomolecular Resource Facilities. (March 2022) - Cole, Richard W.; Kubow, Kristopher E.; Ngila, Jane Catherine
Abstract : Abstract: The Association of Biomolecular Resource Facilities (ABRF) members typically work in cores (shared resources) or in support of them. ABRF's mission is to define excellence for shared resources worldwide. While our vision is to accelerate breakthroughs in scientific discovery, ABRF is committed to advancing the integration of technologies, education, communication, and reproducible research in the operations of shared scientific resources worldwide. Our members support best practices, research excellence, and reproducibility in scientific discovery. ABRF promotes a collaborative community that cultivates professional development and technological innovation. This document outlines a number of things about ABRF, including ABRF's mission and value statements, examples of its research groups and activities, an example of an ABRF outreach program to inform and guide the scientific community about optimization of shared resources nationwide, and an example of an international outreach and collaborative program with like-minded colleagues and organizations in Africa.